2021
DOI: 10.1002/cjoc.202000741
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Asymmetric Hydrogenation of 2‐Phenyl Acrylic Acids Catalyzed by a Rh(I) Catalyst with Ferrocenyl Chiral Bisphosphorus Ligand: The Role of Ion‐Pair Interaction

Abstract: Hydrogenation| Enantioselectivity| Reaction mechanism| Density functional theory | Ion-pair interactionAsymmetric hydrogenation reaction is one of the most efficient synthetic methods to form useful chiral compounds for synthetic chemistry, medicinal chemistry and material chemistry. Generally, the enantioselectivity of many hydrogenation reactions is controlled by steric hindrance between the chiral ligand and substrate. Recently, Zhang group developed a highly asymmetric hydrogenation of 2-aryl and 2-alkyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…All density functional theory (DFT) calculations were performed with the Gaussian 09 program to examine the stereoselectivity of the intramolecular cyclization of N -benzylfumaramide in the presence or absence of the rotaxane. The M06 method combined with mixed basis sets (BS1:6-31G* for the light elements and SDD for the heavy Cs metal) was employed to fully optimize all the structures of reactants, intermediates, transition states (TSs), and products in the gas phase.…”
Section: Computational Detailsmentioning
confidence: 99%
“…All density functional theory (DFT) calculations were performed with the Gaussian 09 program to examine the stereoselectivity of the intramolecular cyclization of N -benzylfumaramide in the presence or absence of the rotaxane. The M06 method combined with mixed basis sets (BS1:6-31G* for the light elements and SDD for the heavy Cs metal) was employed to fully optimize all the structures of reactants, intermediates, transition states (TSs), and products in the gas phase.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Given the very important applications of these compounds, their asymmetric synthesis has long been a prominent research topic for chemists. Among the reported methodologies, asymmetric hydrogenation, as an efficient and easy-to-industrialize preparation method, is one of the most attractive approaches 7 35 (Fig. 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the hydrogenation of substrates 8 and 9 gave very low ee (Scheme c), indicating that the ion pairing interaction between the ligand and substrate played a very important role in the current reaction . A recent computational study by Chung and Dong as well as their co-workers revealed the role of the ion pairing interaction in a similar reaction …”
mentioning
confidence: 95%
“…17 A recent computational study by Chung and Dong as well as their co-workers revealed the role of the ion pairing interaction in a similar reaction. 18 A gram-scale synthesis with a low catalyst loading of 0.05 mol % (S/C = 2000) was then conducted to demonstrate the efficiency of the catalyst system using 4a as the model substrate. To our delight, the product 5a was synthesized with c The enantiomeric excess was determined by HPLC on a Chiralcel chiral OJ-3 column.…”
mentioning
confidence: 99%